Tu i teraz, bez obaw i oczekiwań. Praktyka medytacyjna a orientacja temporalna - Rydzewska, Magdalena (Acta Universitatis Lodziensis. Folia Psychologica, 2011)
The article is focused on the relationship between meditation, degree of involvement in the practice and temporal orientation, in particular active concentration on present time called “Carpe diem”. Two hypotheses are tested: a) Practitioners, as compared to nonpractitioners, are presenting significantly higher active concentration on the present and lower orientation on the past, future and present fatalistic orientation; b) If involvement in meditation increases, active concentration on the present also increases. A survey has been carried out on a group of 160 practitioners of Karma Kagyu linage of Tibetan Buddhism in Poland and a group of 100 nonpractitioners. The results suggest, practitioners are more actively focused on present time and this active concentration increases with involvement in meditation.